2015
DOI: 10.1007/s00586-015-4191-8
|View full text |Cite
|
Sign up to set email alerts
|

Lavage prior to vertebral augmentation reduces the risk for cement leakage

Abstract: Vertebral body lavage prior to cement augmentation is a safe technique to reduce cement leakage in a clinical setting and has the potential to prevent pulmonary fat embolism. Moreover, a better filling pattern can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
(43 reference statements)
0
24
0
1
Order By: Relevance
“…The surgical technique used in the current study is designed to minimize implant leakage by preparing the vertebral body prior to injection with saline lavage. This technique has been shown to significantly reduce leakage frequency while improving cement distribution within the vertebral body [15]. It is hypothesized that saline lavage removes marrow, fat, and soft tissue elements from the vertebral body, leading to a measurable decrease in pulmonary fat emboli during cement injection into a vertebral body [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical technique used in the current study is designed to minimize implant leakage by preparing the vertebral body prior to injection with saline lavage. This technique has been shown to significantly reduce leakage frequency while improving cement distribution within the vertebral body [15]. It is hypothesized that saline lavage removes marrow, fat, and soft tissue elements from the vertebral body, leading to a measurable decrease in pulmonary fat emboli during cement injection into a vertebral body [21].…”
Section: Discussionmentioning
confidence: 99%
“…Two 11G bone access cannulas were placed in the anterior half of the vertebral body through the pedicles. Saline lavage was performed as described by Hoppe et al by first attaching one 20 mL syringe containing 10 mL of saline to one access cannula while an empty 20 mL syringe was attached to the contralateral cannula [15]. A slight vacuum was then applied to the empty syringe as gentle pressure was applied to inject saline from the opposite syringe to pull marrow, fat, and soft tissue from the vertebral body.…”
Section: Treatment Proceduresmentioning
confidence: 99%
“…Previously reported lavage methods involved bilateral operation [8,9,10] , but unilateral pulsed jet *Significant difference…”
Section: Introductionmentioning
confidence: 99%
“…However, leakage during PVP or PKP remains a concern among surgeons. Some studies have shown that intravertebral lavage prior to cement injection can effectively remove vertebral fat and bone marrow and reduce the morbidity of extravasation [6,7] .Previously reported lavage methods involved bilateral operation [8,9,10] , but unilateral pulsed jet *Significant difference…”
mentioning
confidence: 99%
“…Some studies have shown that intravertebral lavage prior to cement injection can effectively remove vertebral fat and bone marrow and reduce the morbidity of extravasation [6,7] . Previously reported lavage methods involved bilateral operation [8,9,10] , but unilateral pulsed jet lavage method has not been described. Thus, we designed and used a unilateral pulsed jet lavage system to investigate the effect of unilateral irrigation prior to vertebroplasty on leakage, intravertebral pressure, and cement distribution.…”
Section: Introductionmentioning
confidence: 99%